Gestão de bens comuns e inovação social : o caso do Banco Comunitário dos Cocais - Farias, Magno Willams de Macêdo (2018)
Faced with the exclusion promoted by the conventional financial system (public and private banks) due to the criteria of selectivity, guarantees required and margins of financial return pursued by these institutions, a large part of the Brazilian population does not have access to banking services. They are people living in extreme poverty, especially those living in communities far from the urban centers of Brazilian cities. For this part of the population, alternatives have recently appeared that try to democratize access to financial resources, which are treated as a common good, that is, of collective use, especially for small-scale economic units, using innovations by a multiplicity of institutional arrangements and new governance mechanisms such as innovations in the field of solidarity finance, in particular the Community Development Banks (DCBs). From this context, the present study sought to understand the nature of innovation and the challenges raised in the management of solidarity finance services, carried out through Community Banks as a modality of a common good. To achieve this objective, a single case study was carried out at the Cocais Community Bank, located in the municipality of São João do Arraial, in the state of Piauí. This study has a qualitative character, with a descriptive and exploratory approach. Data were collected through semi-structured interviews, documentary research and non-participant observation, and were analyzed through narrative. The Cocais bank was built by its own users, in order to solve the problem of lack of access to financial services in the municipality, especially for the part of the population excluded from the conventional banking system, having as mechanisms of access the social utility of these services, in particular solidarity credit, respecting the socio-cultural characteristics of the territory belonging to its users, defining it as a social innovation. Challenges related to: (a) the process of constructing the initiative, conflicts related to political issues in the territory, challenges regarding acceptance of the social currency, limiting the credit fund, and the demobilization of the population in relation to the management of the bank. These challenges express the complexity of resource management in common use.